A novel pathogenic mechanism for cerebellar lesions produced by Solanum bonariense in cattle. (May 2015) - Verdes, José Manuel; Márquez, Mercedes; Calliari, Aldo; Battes, Daniel; Moraña, José Antonio; Gimeno, Eduardo Juan; Odriozola, Ernesto; Giannitti, Federico; Guerrero, Florentina; Fidalgo, Luis Eusebio; Pumarola, Martí
Intoxication with Solanum bonariense in cattle causes cerebellar cortical degeneration with perikaryal vacuolation, axonal swelling, and death primarily of Purkinje cells, with accumulation of electron-dense residual storage bodies in membrane-bound vesicles. The pathogenesis of this disease is not fully understood. Previously, we proposed that inhibition of protein synthesis in Purkinje cells among other altered metabolic pathways could lead to cytoskeletal alterations, subsequently altering cell-specific axonal transport. In the present study, immunohistochemical and histochemical methods were used to identify neuronal cytoskeletal alterations and axonal loss, demyelination, and astrogliosis in the cerebellum of intoxicated bovines. Samples of cerebellum from 3 natural and 4 experimental cases and 2 control bovines were studied. Immunoreactivity against neurofilament (NF)-200KDa confirmed marked loss of Purkinje neurons, and phospho-NF protein, β-tubulin, and affinity reaction against phalloidin revealed an altered perikaryal distribution of neuronal cytoskeletal proteins in the remaining Purkinje cells in intoxicated cattle. Reactive astrogliosis in every layer of the cerebellar cortex was also observed with anti–glial fibrillary acidic protein immunohistochemistry. In affected cattle, demyelination and axonal loss in the cerebellar white matter, as well as basket cell loss were demonstrated with Klüver–Barrera and Bielschowsky stains, respectively. Based on these results, we propose that neuronal cytoskeletal alterations with subsequent interference of the axonal transport in Purkinje cells may play a relevant role in the pathogenesis of this neurodegenerative disorder, and also that demyelination and axonal loss in the cerebellar white matter, as well as astrogliosis in the gray matter, likely occur secondarily to Purkinje cell degeneration and death.